2014
DOI: 10.1002/pola.27410
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unsaturation containing P(VDF‐co‐TrFE‐co‐CTFE) from P(VDF‐co‐CTFE) in one‐pot catalyzed with Cu(0)‐based single electron transfer living radical polymerization system

Abstract: Poly(vinylidene fluoride-co-trifluoroethylene-co-chlorotrifluoroethylene) (P(VDF-co-TrFE-co-CTFE)) with internal double bond has been reported with high dielectric constant and energy density at room temperature, which is expected to serve as a promising dielectric film in high pulse discharge capacitors. An environmentally friendly one-pot route, including the controllable hydrogenation via Cu(0) mediated single electron transfer radical chain transfer reaction (SET-CTR) and dehydrochlorination catalyzed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Under the ATRP reaction conditions, internal unsaturation can occur by the β-hydrogen elimination mechanism, as previously reported. 44,45 By comparing the peak integrals in the 1 H NMR spectra, the chemical compositions of P(VDF-CTFE)-g-PFMMAs were obtained, and they are listed in Table 1; these were further confirmed from the 19 F NMR spectra (Figure 1c). The mole fraction of reacted CTFE and the average numbers of attached monomers in a side chain ranged from 9.3 to 11.1 mol % and 10.6 to 13.8 mol %, respectively, although the mole fraction of the generated double bond was in the range of 4.0−7.0 mol %.…”
Section: Resultsmentioning
confidence: 89%
“…Under the ATRP reaction conditions, internal unsaturation can occur by the β-hydrogen elimination mechanism, as previously reported. 44,45 By comparing the peak integrals in the 1 H NMR spectra, the chemical compositions of P(VDF-CTFE)-g-PFMMAs were obtained, and they are listed in Table 1; these were further confirmed from the 19 F NMR spectra (Figure 1c). The mole fraction of reacted CTFE and the average numbers of attached monomers in a side chain ranged from 9.3 to 11.1 mol % and 10.6 to 13.8 mol %, respectively, although the mole fraction of the generated double bond was in the range of 4.0−7.0 mol %.…”
Section: Resultsmentioning
confidence: 89%
“…This Cu(I)-mediated process required relative high catalyst loading and elevated reaction temperature to initiate the less active C–Cl bond in P(VDF- co -CTFE) backbone, which resulted in unexpected chain transfer reactions and dehydrochlorination reactions [ 56 ]. Cu(0)-mediated RDRP of acrylonitrile (AN) and methyl methacrylate (MMA) in the presence of P(VDF- co -CTFE) allowed colorless and purer P(VDF- co -CTFE)- g -PAN and P(VDF- co -CTFE)- g -PMMA copolymers for its mild reaction conditions and lower catalyst concentration [ 57 , 58 , 59 ]. Improvements were achieved by transferring the polymerization from a batch reactor to a copper tubular reactor, such as diminished inconsistent induction time, suppressed “hot spot” effect, and decreased copper and ligand concentration [ 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Newman reported that the ferroelectric nature and piezoelectric properties increased with the increasing of hydrogen bond and dipole density for polyamides . For odd polyamides, the NH and CO groups can fully form hydrogen bonds between molecular chains . Figure shows the structure of hydrogen bond between molecular chains for polyamide 11 (PA11), polyamide 9 (PA9), polyamide 7 (PA7), and polyamide 3 (PA3), in which the hydrogen bond density increases with the decreasing of methylene in molecular chains.…”
Section: Introductionmentioning
confidence: 99%